HUBUNGAN PENDIDIKAN BERKELANJUTAN DENGAN KOMPETENSI SISWA PERAWAT DI INSTITUSI KESEHATAN DELI HUSADA DELITUA TAHUN 2019 - Tedty Rohaya Tinambunan; Anita Theresia Lumban Gaol (Jurnal Penelitian Keperawatan Medik, 2019)
“Sustainable nursing education is professional development that includes a variety of activities carried out by someone in his capacity as a nurse practitioner, in order to maintain and enhance their professionalism as nurses according to established competency standards. The purpose of this study is to find out the relationship between continuing education and nurse competency at inHealth Institute of Deli Husada DelituaThis type of research is an analytical survey with a cross sectional approach. The technique used in sampling is total sampling, namely the total sampling technique with a sample size of 48. The result of this study indicate that there is a continuing educational relationship with nurse.The conclusion of this study is the relationship between continuing education and the competence of nurses at inHealth Institute of Deli Husada Delitua. Advice that can be given is that the institution continues to provide and include nurses in continuing education to assist nurses in developing their competence”.